Implementation Of Bank Indonesia’s Financial Accounting Policies: A Descriptive Analysis From Regulatory And Practical Perspectives - Ardista, Dwitya Rizki; Rahmanti, Virginia Nur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Bank Indonesia (BI) requires a specialized accounting standard aligning with its unique central bank characteristics. This study analyzes the implementation of the Bank Indonesia Financial Accounting Policy (KAKBI) as a replacement for the Bank Indonesia Financial Accounting Guidelines (PAKBI) through a case study at BI's Central Office in Jakarta. The main differences between KAKBI and PAKBI lie in recognizing unique transactions, such as managing currency in circulation, which is recorded as liabilities in KAKBI, and simplifying financial reporting. KAKBI is designed to reflect BI's role through relevant and transparent financial statements. The study also identifies transitional challenges, such as changes in employee mindset and adjustments in information technology. It is recommended that BI intensify public dissemination of KAKBI.